Novel primer specific false terminations during DNA sequencing reactions: danger of inaccuracy of mutation analysis in molecular diagnostics. Issue 5 (October 1996) - Anwar, R; Booth, A; Churchill, A J; Markham, A F
Abstract : The determination of nucleotide sequence is fundamental to the identification and molecular analysis of genes. Direct sequencing of PCR products is now becoming a commonplace procedure for haplotype analysis, and for defining mutations and polymorphism within genes, particularly for diagnostic purposes. A previously unrecognised phenomenon, primer related variability, observed in sequence data generated using Taq cycle sequencing and T7 Sequenase sequencing, is reported. This suggests that caution is necessary when interpreting DNA sequence data. This is particularly important in situations where treatment may be dependent on the accuracy of the molecular diagnosis.